2020
DOI: 10.3389/fnins.2020.00124
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Change Responses to Amplitude Modulation in Cochlear Implant Users: Relationships to Speech Perception

Abstract: Objectives: The ability to understand speech is highly variable in people with cochlear implants (CIs) and to date, there are no objective measures that identify the root of this discrepancy. However, behavioral measures of temporal processing such as the temporal modulation transfer function (TMTF) has previously found to be related to vowel and consonant identification in CI users. The acoustic change complex (ACC) is a cortical auditory-evoked potential response that can be elicited by a "change" in an ongo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 58 publications
4
24
0
Order By: Relevance
“…The ACC does not require the individual’s attention to the stimuli or behavioral response and thus is suitable for difficult-to-test patients. The ACC measures (e.g., the minimum sound change that can evoke an ACC, the ACC peak amplitudes and latencies) were found to be in agreement with the behavioral performance of auditory discrimination tasks ( Martin, 2007 ; Mathew et al, 2017 ; Han and Dimitrijevic, 2020 ). The ACC has shown to be reliable in normal hearing listeners, individuals with hearing loss, and CI users ( Tremblay et al, 2003 ; Friesen and Tremblay, 2006 ; Martin, 2007 ; Martinez et al, 2013 ; Mathew et al, 2017 ).…”
Section: Introductionsupporting
confidence: 56%
“…The ACC does not require the individual’s attention to the stimuli or behavioral response and thus is suitable for difficult-to-test patients. The ACC measures (e.g., the minimum sound change that can evoke an ACC, the ACC peak amplitudes and latencies) were found to be in agreement with the behavioral performance of auditory discrimination tasks ( Martin, 2007 ; Mathew et al, 2017 ; Han and Dimitrijevic, 2020 ). The ACC has shown to be reliable in normal hearing listeners, individuals with hearing loss, and CI users ( Tremblay et al, 2003 ; Friesen and Tremblay, 2006 ; Martin, 2007 ; Martinez et al, 2013 ; Mathew et al, 2017 ).…”
Section: Introductionsupporting
confidence: 56%
“…The ACC has been successfully used as an electrophysiological measure of gap detection 33 , frequency change detection 34 , and the eACC for electrode discrimination [35][36][37] in CI users. Furthermore, the eACC N1 amplitude shows a similar pattern as the temporal modulation transfer function of CI users 38 . It is, however, unclear if the eACC is able to reflect the TEM encoding ability of the stimulated neural ensembles of an individual CI user.…”
mentioning
confidence: 58%
“…Nevertheless, Mathew et al 35,36 successfully used the eACC to assess electrode www.nature.com/scientificreports/ discrimination, and as long as the alteration made between two alternating stimuli cannot be attributed to confounding factors, this can be a clinically relevant measure which is little troubled by the stimulation artifacts. The electrophysiological measures used in the present study originate from regions in the auditory pathway beyond the periphery 17,38 and are assumed to reflect the processing cascade of all neural ensembles involved in TEM encoding of the ascending auditory pathway up to generator of the neural response. It is therefore difficult to derive from these measures where in the ascending auditory pathway TEM encoding is affected.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that CI listeners can make considerable use of AMs to assist with speech recognition (Shannon et al, 1995), as evidenced by some remarkable early studies that showed implant recipients could obtain a degree of speech understanding with only a single channel device (Tyler, 1988;Rosen et al, 1989;Rosen, 1992). This demonstrates that a large proportion of the information necessary for successful speech recognition is associated with the modulating envelope of speech signals (De Ruiter et al, 2015;Dimitrijevic et al, 2016;Han and Dimitrijevic, 2020). Therefore, it is plausible that poor speech performance amongst CI users could result from inadequate transmission of the AM signal from the CI to the brain.…”
Section: Introductionmentioning
confidence: 99%